Análise de intoxicação por Benzeno: uma revisão bibliográfica - MARIA, Camila Rodrigues Thom (2021)
Benzene is a hydrocarbon used in several occupational processes, like the petrochemical industry, tire shops, steelworks and gas stations. This xenobiotic is known for its carcinogenic and hematotoxic potential. Workers that deal directly with benzene are the most exposed population, being able to suffer from decrease of blood cells, histologic damage and mutations. This research has its goals in identifying the chronic and acute effects caused by the intoxication; concerning DNA Alterations; analyze the most used biomarkers; epidemiological data and legislation about benzene. To carry out this work, we proposed a methodology that is focused on a bibliographic review, based on articles published in the last two decades, selected according to its relevance to the objectives already presented. The results confirm that through this long term exposition, workers may present pancytopenia, chromosomal alteration, leukemia development and that there are new biomarkers that are more reliable to detect the xenobiotic exposition. The results also show that white blood cells are the most affected, the biomarker trans-trans muconic acid may suffer external interference, making it a marker with low sensibility for low exposure dose and the epidemiological data associated with researches confirms that in a long term exposure benzene may lead to the development of leukemia, however, the process in which the xenobiotic works in the body is still not clear. It is important to mention that we only counted with individual protection equipment, ambiental supervision, oversight and regular exams to avoid intoxication.